Horses with solar foot penetration, deep digital flexor tendon injury, and absence of concurrent synovial sepsis can have a positive outcome. Issue 6 (29th August 2018) - Schiavo, Stefano; Cillán‐García, Eugenio; Elce, Yvonne; Liuti, Tiziana; Taylor, Sarah E.
Abstract: Solar foot penetration is one of the causes of deep digital flexor tendon injuries in horses, however, limited information is available on the prognosis for return to soundness in the absence of synovial sepsis. Objectives of this retrospective observational study were to describe low‐field magnetic resonance imaging (MRI) findings and long‐term outcome for a group of horses with this combination of clinical problems. Horses were included if low‐field standing MRI of the foot was performed following puncture wounds, injury of the deep digital flexor tendon was diagnosed, and sepsis was confirmed to be absent in all adjacent synovial structures (distal interphalangeal joint, navicular bursa, and digital flexor tendon sheath). Medical records were reviewed and MRI studies were re‐interpreted. Follow‐up information was obtained via a telephone questionnaire at a minimum of 6 months post‐injury. A total of 11 horses met inclusion criteria. In three horses, the deep digital flexor tendon injury was only visible in the T2 fast spin echo sequence and contrast radiography improved diagnostic certainty. The most commonly affected area was between the distal border of the distal sesamoid bone and the facies flexoria of the distal phalanx (6/11, 55%). Six horses (60%) had an excellent outcome (5, show jumping; 1, general purpose) and returned to full athletic function. Five horses (40%) were sound but had not yet resumed full work at the time of follow‐up. Findings indicated that the prognosis for return to soundness can be good for horses with solar penetration, deep digital flexor injury, and absence of synovial sepsis.